Genotype-phenotype relationship in Iranian patients with cystic fibrosis - Najafi, Mehri; Alimadadi, Hosein; Rouhani, Pejman; Kiani, Mohammad Ali; Khodadad, Ahmad; Motamed, Farzaneh; Moraveji, Alireza; Hooshmand, Masoud; Ashtıani, Mohammad Taghi Haghi; Rezaei, Nima (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Cystic fibrosis (CF), the most common hereditary, life-threatening disease, is caused by a mutation in the CFTR gene. Because different mutations can affect clinical manifestations of patients, this study was conducted to investigate the possible genotype-phenotype relationship in a group of Iranian patients with CF. Materials and Methods: This case-series study was conducted in 30 patients with CF who were referred to a tertiary pediatric hospital in Tehran. In this study, the DNA of the patients was evaluated for delta F508 mutation, whereas some parameters such as the age at diagnosis, the sweat chloride level, and clinical manifestations related to pancreatic insufficiency and pulmonary involvement were also assessed. Results: Among all the studied patients, 16.6% had a delta F508 mutation, either homozygote or heterozygote. The mean age at diagnosis was lower in patients with the delta F508 mutation, but the sweat chloride level tended to be higher in these patients. All the patients with the delta F508 mutation had exocrine pancreatic insufficiency, which tended to be higher than 84% in those without this mutation. In addition, all of these patients had pulmonary involvement, which tended to be higher than 64% in those with negative delta F508 mutation. Conclusion: According to the results of this study, the frequency of delta F508 mutations in Iranian patients appears to be much lower than what is seen in American and the European patients. In those with the delta F508 mutation, pulmonary involvement and pancreatic insufficiency are more common; the sweat chloride level tended to be higher, but the age at diagnosis was lower, all of which resemble a more severe form of disease.